Peri-partum cardiomayopathy-not a rare entity, clinical profile in a rural tertiary care center in Gujarat, India - Bhattacharjee, Rumi; Raithata, Nitin; Patel, Molina; Vaishnav, Smruti (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Peri-partum cardiomayopathy (PPCM) in pregnancy has a potential to adversely affect both mother and fetus. Severe cases can be associated with life threatening complications unless managed promptly by multidisciplinary team. The objective was to study maternal and fetal outcome of PPCM patients. Methods: An observational cohort over 4 years (2012 to 2015) was conducted in a Rural tertiary care center. Consecutive antenatal and postpartum women with PPCM were studied for medical and obstetric complications, deliveries, fetal outcome and maternal mortality. Results: The incidence of PPCM was 0.3% and Most patients presented with typical signs and symptoms of heart failure. 55.5% were in NYHA 3 and 4 and 50% had ejection fraction below 30%. 83.3% required ICU admissions of varying length and Maternal mortality was in 1 patient (5.56%). PPCM occurred in 55.5% of ante partum against 44.4% of postpartum patients. Obstetric complications like PPH occurred in 11.1% while poor fetal outcome like preterm deliveries occurred in 50% while still births in 16.67%. Conclusions: The low incidence and rarity of PPCM presents itself with diagnostic dilemma. Obstetrician should have high index of suspicion in patients with heart failure and high risk factors. Early diagnosis and prompt treatment can only improve the outcome.